Research on the teaching of history in the state meetings on history of the ANPUH-BA: initial impressions - Lima Ferreira, Carlos Augusto; Silva Teles, Adriana; Cerqueira, Dulcinea; Dos Santos Marques, Edicarla (Universidad Pedagógica y Tecnológica de Colombia, 2018)
This research project is carried out in the area of the teaching of history. The primary source of this research was the annals of the seven editions of the State Meeting on History in Bahia; the works consulted being the published articles and the approved summaries. This article seeks to analyze the communications presented in the Anpuh-Bahia between 2002 and 2014. This research contemplated themes related to the object of study, including the products of research in the academic and school environment, regarding the teaching of history in Bahia. The results show that there is Little information on topics related to the teaching of history. The texts do not relect the debate about the teaching of history and show the dichotomy between the Teaching of History vs Research and Historiography, or Undergraduate degree vs Secondary school.